La population Chasséenne du gisement du Crès (Hérault): caractéristiques métriques et anatomiques - Aurore Schmitt (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The  archaeological  settlement  of  the  Crès  (Hérault),  dating  to  the  ancient  Chassean,  produced  49  individuals (27 adults and 22 immature subjects). This series is the most important for this chronological period in the south of France and enables characterization of  the biological variability of  the population of  the site  through study of  the osteometric features  and  the  anatomical  variations. These  individuals  are  characterized  by  a  small  stature,  a  pronounced  sexual dimorphism in the size of the long bone and slender lower limbs. However, the robustness indexes do not vary between sexes. The long bone measurements of one of the males lie outside the variability within the group. The frequency of some anatomical variations differs from those observed in modern populations.